Menjaga Asa UMKM dan Kebangkitan Kuliner Lokal: Sosialisasi, Edukasi, dan Pendampingan Sertifikasi Halal terhadap Pegiat UMKM di Lereng Gunung Bromo - Sukmawan, M.Pd, Dr. Sony; Sucipto, Sucipto; Tawakal, Goerge Towar Ikbal; Ardhian, Dany; Isna, Fariha Nurul; Izza, Siti Fitrohitul; Rufianjani, Esavalin Oktavia; Mumtaz, Tsabitah Zain; Azya, Zahra Kasfillah (Jurnal Gramaswara: Jurnal Pengabdian kepada Masyarakat, 2024)
Halal cullinare has become a necessity, especially in tourist areas. Therefore, halal certification is required, especially in locations with a majority non-Muslim population. Besides ensuring halal status, halal certification also serves as a means to promote local cullinare promising economic growth for the local community while preserving the rich culinary heritage. This community service project focuses on three villages on the slopes of Mount Bromo, namely Ngadiwono Village, Tlogosari, and Mojorejo. The program took place on June 25-26, 2023, with a primary focus on the Tosari Village rest area, in collaboration with the Baladaun community, local tourism communities (Pokdarwis), women's organizations (ibu-ibu PKK), and local SMEs (UMKM). Several activities have already been carried out, including the dissemination and education about halal certification, with experts and halal certification consultants from Brawijaya University invited to provide guidance. As a follow-up, the community service team will compile a halal certification guidebook containing instructions on administrative preparation, applying for halal certification through the Ministry of Religious Affairs' provided application, and providing assistance in preparing the necessary documentation for submission through the application. Keywords: halal sertification; Bromo Mountain; local culinary; Brawijaya University; community services